EVALUATION OF DIETARY INTAKE OF ADOLESCENT ATHLETES FROM A JUDO TEAM - Alberto Dalla Costa Junior, Luiz; Assoni Bilibio, Sarah; Antoniazzi dos Santos, Pâmela (Health and Society, 2023)
Introduction: Judô is a dynamic sport, high intensity and required skills to perfect techniques. Objective:The aim of the present study was assessments the nutritional profile of adolescent judo athletes and compare with recommended in the literature. Material and Methods: Cross sectional study with convenience sample composed by 12 male adolescents with age of 13-18 years, active in judo competition in the last 6 months. The nutritional assessment was realized by the instrument 24h recovery. Was collected 3 interview for obtection of medium consumption. Results: The sample demonstrated the average energy deficit of 1450,95 Kcal, average intake of carbohydrate ingested was 314,04g, that of protein 93,19g and lipids was on average 27.12% of the energy consumed. In Average 57,45% of the athletes was inadequate fiber consumption and 46,57% inadequate calcium. In contrast the iron and zinc was ultra passed in 43,74% and 22,54% respective. Conclusion:The authors highlight the importance of seeking professional nutritionists, able to absorb the individual needs of each team, providing guidance on how should be an ideal diet to maintain health and performance for this age group.